plz help to solve this
Attachments:
![](https://hi-static.z-dn.net/files/d0c/3140b43935a9ec385cb32a113b3c7c6e.jpg)
Answers
Answered by
1
Answer:
lim x=> 3 1/(x - 3) - 2/(x²-4x + 3)
=> lim ₓ→₃ x² - 4x + 3 - 2(x-3)/(x-3)(x²-4x+3)
lim ₓ→₃ x² - 4x + 3 -2x + 6/(x-3)(x²-4x+3)
lim ₓ→₃ (x²- 6x +9) / (x-3)(x² -4x +3)
lim ₓ→₃ (x - 3)² / (x-3)(x²-3x-x+3)
lim ₓ→₃ (x-3)(x-3) / (x-3)(x-3)(x-1)
lim ₓ→₃ 1/(x-1) [( x - 3) cancels out in Nr & Dr ]
=> 1/(3-1) [substituting x = 3 the limiting value ]
=> 1/2 Answer
Answered by
1
Answer:
Attachments:
![](https://hi-static.z-dn.net/files/d5a/81d54d7d14a55ae03541fb7242c645b5.jpg)
Similar questions
Math,
6 months ago
Science,
6 months ago
Physics,
6 months ago
India Languages,
1 year ago
India Languages,
1 year ago
Biology,
1 year ago
Biology,
1 year ago